2018
DOI: 10.21149/9082
|View full text |Cite
|
Sign up to set email alerts
|

Factores pronósticos en pacientes con cáncer de mama y metástasis cerebral como primer sitio de recurrencia

Abstract: Objetivo. Evaluar los factores pronósticos (características clínico-patológicas y tratamientos) en las pacientes con cáncer de mama y metástasis al sistema nervioso central (SNC) como primer sitio de afección. Material y métodos. Cohorte retrospectiva, formada por 125 pacientes con cáncer de mama atendidas en el Instituto Nacional de Cancerología durante 2007-2015, quienes presentaron afección en el SNC como primer sitio de metástasis. A través del método Kaplan-Meier y tablas de vida se estimó la supervivenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that a large tumor burden ( 17 , 18 ), axillary lymph involvement, high tumor number ( 18 , 19 ), high histological grade ( 17 ), triple-negative breast cancer ( 18 , 20 ), high Ki67 index ( 21 ), BRCA1 mutation ( 22 ) and breast cancer metastasis to the CNS ( 20 ) are associated with reduced survival time in breast cancer. The present case was consistent with these findings, although the BRCA gene was not tested for in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that a large tumor burden ( 17 , 18 ), axillary lymph involvement, high tumor number ( 18 , 19 ), high histological grade ( 17 ), triple-negative breast cancer ( 18 , 20 ), high Ki67 index ( 21 ), BRCA1 mutation ( 22 ) and breast cancer metastasis to the CNS ( 20 ) are associated with reduced survival time in breast cancer. The present case was consistent with these findings, although the BRCA gene was not tested for in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer continues to be the leading cause of cancer death in women in the world, mainly in emerging economies such as Mexico. In this regard, various authors have analyzed and measured the presence of autoantibodies in various types of cancer (including breast cancer), and some have even evaluated the effectiveness for the recognition of breast cancer antigens [3,4]. Even though their concentration and variety differ significantly among subjects, the fact that autoantibodies' individual patterns remain relatively stable throughout life but shift when the individuals begin developing a disease or if they become ill led us to think that they may be used as biomarkers [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Given the relatively high morbidity and mortality rates associated with BC, public health systems around the world have implemented programs to increase the life expectancy of women, based on timely diagnosis after periodic physical examination of the breasts, image-based screening, and identification of blood molecular markers. Unfortunately, this strategy has been insufficient in decreasing BC morbidity and mortality, especially in countries with developing economies, where population-wide medical mentoring and education is deficient, and the population has limited access to screening programs and treatments [3].…”
Section: Introductionmentioning
confidence: 99%